Evaluation of a Furniture Product Testing Process and Results Reporting Application using the Extended Technology Acceptance Model (TAM) at XYZ Company - Faizal Asrul Pasaribu; Jumadi Simangunsong; Kiki Puspo Arianty (SISTEMASI, 2026)
The furniture manufacturing industry demands efficient internal processes and reliable reporting quality; however, the adoption of digital reporting applications is often hindered by user acceptance factors. This study evaluates user acceptance of a Furniture Product Testing Process and Results Reporting Application at PT XYZ using the Extended Technology Acceptance Model (ETAM), which integrates constructs from the Technology Acceptance Model (TAM) and variables from the Information System Success Model (ISSM), including system quality, information quality, service quality, and user satisfaction. A survey of employees across operational units was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The measurement model met the criteria for validity and reliability (AVE = 0.598–0.875; composite reliability = 0.869–0.954). The coefficient of determination (R²) indicates a strong to very strong model across key variables (R² for intention to use = 0.883; attitude toward use = 0.738; perceived ease of use = 0.737; perceived usefulness = 0.788; actual use = 0.698). The main results reveal significant paths: system quality → perceived ease of use (β = 0.563; p < 0.007), perceived ease of use → attitude toward use (β = 0.735; p < 0.001), attitude toward use → behavioral intention (β = 0.940; p < 0.001), and behavioral intention → actual use (β = 0.828; p < 0.001). In contrast, information quality and service quality do not have a significant effect on perceived usefulness, perceived ease of use, or user satisfaction; additionally, perceived usefulness and user satisfaction do not significantly drive actual use. These findings highlight the central role of system performance and usability in shaping sustained adoption. They also suggest the need for enhanced training strategies and clearer communication of system benefits to strengthen perceived usefulness and to ensure that service support contributes more effectively to user satisfaction and system usage.